Blood Transfusion in End-of-Life Cancer Care: Clinical Evidence, Patient Blood Management and Goal-Concordant Practice - Saikat Mandal; Manideepa Maji; Ashish Sharma; Arkadeep Dhali (Medical Sciences, 2026)
Blood transfusion near the end of life for patients with cancer may relieve symptoms attributed to anaemia or control bleeding, but its palliative value depends on whether benefit occurs within the patient’s expected survival and outweighs the clinical and practical burden of treatment. This structured narrative review examines evidence concerning red-cell and platelet transfusion, transfusion-sparing patient blood management, hospice access and alternative delivery models in adults receiving palliative or end-of-life care. Structured searches of MEDLINE, Embase, Scopus and the Cochrane Library identified original studies, audits, qualitative research and relevant evidence syntheses. The evidence was predominantly observational and methodologically heterogeneous. Reported symptomatic response rates after red-cell transfusion ranged from 31% to 70%, most commonly involving short-term improvement in fatigue, dyspnoea or general well-being. Benefit often diminished within 14 days, while 23–35% of participants in historical cohorts died within two weeks, limiting the opportunity to experience benefit. Response was not reliably predicted by haemoglobin concentration. Red-cell transfusions were frequently guided by laboratory values, administered late in the disease course and not followed by systematic reassessment. Evidence concerning platelet transfusion remains largely descriptive and does not establish a prophylactic threshold for end-of-life care. Intravenous iron and haemostatic radiotherapy may reduce transfusion requirements in selected patients, although their applicability depends on clinical stability, the source of bleeding and sufficient time to benefit. In haematological malignancies, transfusion dependence has been associated with lower hospice enrolment and shorter hospice stays, whereas home- and hospice-based transfusion may reduce travel and waiting burdens for appropriately selected patients. Transfusion near the end of life should therefore be considered a goal-concordant, time-limited trial. A patient-valued outcome should be defined beforehand, the fewest units likely to achieve that outcome should be administered, and benefit should be reassessed using the same measure. Further transfusion should be offered only when documented symptomatic or functional benefit outweighs adverse effects and treatment burden for the individual patient.